Impact of of good practices of handling training on beef cattle welfare and stockpeople attitudes and behaviors - Ceballos, Maria C. [UNESP]; Sant'Anna, Aline C. [UNESP]; Boivin, Xavier; Costa, Franciely de Oliveira [UNESP]; Carvalhal, Monique V. de L. [UNESP]; Paranhos da Costa, Mateus J. R. [UNESP] (Elsevier B.V., 2018)
The aims of this study were to evaluate the potential impacts of training in good practices of cattle handling on stockpeople's attitudes and behavior, and on cattle welfare, in Brazilian beef farms. Additionally, we aimed to investigate whether the quality of cattle handling deteriorates as the working day progresses. The study was conducted on 24 commercial beef cattle farms (located in Northeastern Para State, Brazil), which were classified into three groups with different levels of training: Regularly trained (TRAINED-R, n = 9), Occasionally trained (TRAINED-O, n = 9) and Never trained (NON-TRAINED, n = 6). A total of 150 stockpeople working on these farms were categorized according to the level of training received: i) Trained (TS, n = 43), those who attended formal handling skills training; ii) Non-trained, but had close contact with a trained stockperson (CTS, n = 62), and iii) Non-trained, and had no contact with a trained stockperson (NT, n = 45). On each farm, indicators of quality of handling (including animal and stockpeople behavior, and stockpeople attitudes) were measured on one workday, during the vaccination handling procedures of approximately 236 +/- 65 (mean +/- SD) heads of cattle per farm. We observed that NON-TRAINED farms had the poorest quality of handling, as well as more undesirable animal behaviors during handling (P < 0.05), when compared with the other farm categories (TRAINED-R, TRAINED-O). Stockpeople attitudes and behaviors varied according to their degree of training in good practices of beef cattle handling (P < 0.05). People who participated in a formal training course (TS) had the highest positive and the lowest negative behavior and attitude scores, compared with people in the other groups (CTS and NT). We observed an effect of the progression of the workday (P < 0.05) only on NON TRAINED farms, where handling became worse over time. Our results support the hypothesis that training stockpeople in good cattle handling practices leads to better attitudes and behavior toward cattle. Thus, training stockpeople can be an effective and practical strategy to promote positive human-animal interactions on beef cattle farms, improving the quality of life of both animals and workers.
Keywords: Human-animal interaction; Zebu cattle; Quality of handling; Working day time